Innovation in making wet noodles chia seed flour on chemical, physical, and organoleptic quality for the prevention of obesity - Priscilia Reni A.F; Fransisca Shinta Maharini; Rijantono Franciscus Maria (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Excessive fat accumulation due to a prolonged imbalance of energy intake and energy expenditure. Obesity can be controlled with foods high in fiber. The addition of chia seed flour is a food preparation that increases dietary fiber and reduces the risk of obesity. The aim is to determine the effect of adding chia seed flour on physical, chemical, and organoleptic characteristics. This research is a completely randomized design research design. Research location of STIKes Panti Rapih Yogyakarta Culinary Nutrition Laboratory and research time April-August 2022. Data collection technique through tensile strength analysis using the Universal Testing Machine, water content gravimetric method, Soxhlet method fat content test, Kjehdahl method protein test, carbohydrate method by. difference, and testing total dietary fiber content using the AOAC method, determining energy value by calculating the composition of carbohydrates, fats, and proteins, and organoleptic testing using the Hedonic Test. Data were analyzed using ANOVA, Kruskall Wallis, Mann Whitney, Friedman, and Wilcoxon. Statistical results of tensile strength (p=0.546), water content (p=0,066), ash (p=0,101), fat (p=0,297), protein (p=0,244), carbohydrates (p=0,052), energy (p= 0,268), aroma (p=0,181), texture (p=0,358) and taste (p=0,355), dietary fiber (p=0,019), organoleptic appearance (p=0,002) and overall liking (p=0,038). In conclusion, there is an effect of adding chia seed flour on food fiber content, appearance, and overall.